Antimicrobial effect of plasma-activated tap water on staphylococcus aureus, escherichia coli, and Candida albicans - Chiappim, William; Sampaio, Aline da Graça [UNESP]; Miranda, Felipe; Fraga, Mariana; Petraconi, Gilberto; da Silva Sobrinho, Argemiro; Kostov, Konstantin [UNESP]; Koga-Ito, Cristiane [UNESP]; Pessoa, Rodrigo (MDPI, 2021)
In this study, the potential antimicrobial activity of plasma-activated tap water (PAW) was evaluated against Staphylococcus aureus, Escherichia coli, and Candida albicans. For this, PAW was prepared in a gliding arc plasma system using two treatment conditions: stagnant water and water stirring by a magnetic stirrer, called moving water. Subsequently, their oxidation-reduction potential (ORP), pH, electrical conductivity (σ), and total dissolved solids (TDS) were monitored in different areas of the sample divided according to the depth of the beaker. It was observed that PAW obtained in dynamic conditions showed a more uniform acidity among the evaluated areas with pH 3.53 and ORP of 215 mV. Finally, standardized suspensions of Staphylococcus aureus (ATCC 6538), Escherichia coli (ATCC 10799), and Candida albicans (SC 5314) were treated with PAW, and the reduction of viable cells determined the antimicrobial effect. Our results indicate that the tap water, activated by plasma treatment using gliding arc, is an excellent inactivation agent in the case of Staphylococcus aureus and Escherichia coli. On the other hand, no significant antimicrobial activity was achieved for Candida albicans.
Keywords: Atmospheric plasma; Candida albicans; Escherichia coli; Gliding arc discharge; Plasma activated water; Staphylococcus aureus; Tap water